2021
DOI: 10.1088/1751-8121/ac3623
|View full text |Cite
|
Sign up to set email alerts
|

Non-abelian anyons and some cousins of the Arad–Herzog conjecture

Abstract: Long ago, Arad and Herzog (AH) conjectured that, in finite simple groups, the product of two conjugacy classes of length greater than one is never a single conjugacy class. We discuss implications of this conjecture for non-abelian anyons in 2 + 1-dimensional discrete gauge theories. Thinking in this way also suggests closely related statements about finite simple groups and their associated discrete gauge theories. We prove these statements and provide some physical intuition for their validity. Finally, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Moreover, we defined Galois action on the TQFT such that it doesn't change the sign of D (we can consider taking D → −D as a second step, supplementing our Galois conjugation, when exploring particular orbits). 47 Explicitly including a D → −D transformation leads to certain simple extensions of our results.…”
Section: Jhep01(2022)004 6 Conclusionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, we defined Galois action on the TQFT such that it doesn't change the sign of D (we can consider taking D → −D as a second step, supplementing our Galois conjugation, when exploring particular orbits). 47 Explicitly including a D → −D transformation leads to certain simple extensions of our results.…”
Section: Jhep01(2022)004 6 Conclusionmentioning
confidence: 55%
“…Since Galois conjugation fixes rational numbers, it is clear that the space of integral MTCs (i.e., theories whose anyons all have integer quantum dimensions) is closed under it. An important class of integral MTCs are (twisted) discrete gauge theories (see [47,48] for a recent discussion of these theories, their subcategory structure, and their fusion rules). Since there are integral MTCs that are not (twisted) discrete gauge theories [49], we might naively imagine that these theories mix with discrete gauge theories under Galois conjugation.…”
Section: Discrete Gauge Theoriesmentioning
confidence: 99%
“…Both the product of conjugacy classes as well as the tensor product of representations play a crucial role in the fusion rules of line operators in three-dimensional G-TQFTs [9]. In [17], the Arad-Herzog conjecture in finite group theory [18] was studied in the context of three-dimensional topological quantum field theories (TQFTs). It was shown that this conjecture implies special fusion rules for line operators in these TQFTs.…”
Section: Introductionmentioning
confidence: 99%